Intermittent Fasting as An Alternative Diet Strategy for T2DM Patients: A Systematic Review - Nur Kadir, Afrizal; Freitas Babo, Leticia; Khairatun Hisan, Wildani; Setiyowati, Eppy; Nadatien, Ima (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2026)
Type 2 diabetes mellitus is a chronic metabolic disorder that requires lifestyle-based interventions, particularly dietary modification. Intermittent fasting has emerged as a promising approach; however, evidence of its effectiveness remains inconclusive. This research aims to determine how intermittent fasting, implemented as a non-pharmacological dietary strategy, influences metabolic regulation, body composition, and dietary behavior in adults with type 2 diabetes mellitus. This study was designed as a systematic literature review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, focusing on randomized controlled trials (RCTs) published between 2020 and 2025. Comprehensive literature searches were conducted across three primary databases, including PubMed, ScienceDirect, and ClinicalKey. Methodological quality was assessed using the Revised Cochrane Risk-of-Bias Tool (RoB 2), and data were extracted systematically and synthesized narratively. The search identified 382 articles, of which nine RCTs met the inclusion criteria. The results show that 6 out of 9 studies reported statistically significant reductions in HbA1c (p < 0.05), with reductions ranging from -0.91% to -1.9%. Significant weight loss was observed across most studies, ranging from 2.98 kg to 9.7 kg (p < 0.01). Furthermore, lipid profiles showed significant improvements, particularly in triglycerides (p < 0.05) and total cholesterol (p ≤ 0.023) in selected trials. However, none of the reviewed studies examined eating behavior traits, highlighting a research gap. Future studies should explore behavioral and adherence aspects to assess the long-term feasibility of intermittent fasting in diabetes care.